Computer Simulation of Light Propagation in Photonic Waveguide Structures - Plesingr, J.; Ctyroky, J. (Radioengineering Society, 1993)
An interactive program for simulating light propagation through photonic waveguide structures was developed. From the viewpoint of CAD, two parts of this program are interesting: the channel waveguide editor, and the 3D graphic interpretation of the resul